The testimonial narratives of the Tausug survivors during the militarization of Sulu and the 1974 Battle of Jolo: counter-history, identities, and collective memories - Salomon, Elgin Glenn R.
After the declaration of Martial Law, the Armed Forces of the Philippines (AFP) heavily militarized Mindanao including the Sulu archipelago to fight against the growing threats of Moro National Liberation Front (MNLF), a Muslim secessionist group that aimed to make Mindanao independent from the rest of the Philippines. However, the conflict reached its apex on February 7, 1974, when two-third of the town of Jolo in the province of Sulu was razed into ashes when the AFP launched operation Bagsik (Operation Fierce) to retake it from the MNLF.